Investigating the correlation and composition of organic components in ZrO2-based slurry on printability improvement and defect suppression of Vat photopolymerization. (March 2023) - Gong, Huaqiang; Wang, Chengyun; Wu, Han; Luo, Xin; Liang, Jiahua; Li, Nan; Chen, Shenggui; Long, Yu
Abstract: High solid content (52 vol%) zirconia-based slurries were prepared for supportless Vat photopolymerization (VP) 3D printing. The correlation and composition of ZrO2 slurry's organic components, such as dispersant, surface modifier, diluent, and crosslinker, are explored to improve the printability of VP and weaken the defects formation during sintering. The results show that stearic acid (SA) is more suitable than 3-Glycidoxypropyltrimethoxysilane (KH560) as a surface modifier for ZrO2 because of its longer molecular chain alkanes and non-reaction between molecules, which can improve the powder dispersion more effectively. Interestingly, although the commonly used dispersant (BYK111) competes with the surface modifier (SA) in adsorption on the particle surface and the former is more effective in reducing viscosity, it is found that a small amount of SA can enhance the viscosity-reducing effect of BYK111 by increasing the particle dispersion. Moreover, a ratio of 70:30 between diluent and crosslinker is proved to not only enable the slurry to a low viscosity but also allow the green body a high strength (38 ± 6 MPa) to avoid deformation caused by gravity. Also, it is found that using two diluents (1, 6-Hexanediol diacrylate (HDDA) and Morpholine, 4-(1-oxo-2-propenyl) -(9CI) (ACMO)) can weaken defects' formation by increasing the temperature range of organic matter's decomposition. Finally, the densities of the sintered parts are 99.2%, and the three-point bending is 845 ± 124 MPa. This study is believed to provide new insights into the slurry configuration and practical application of ZrO2 . Graphical Abstract: ga1 Highlights: A high-solid content (52 vol%) ZrO2 slurry is prepared for the VP 3D printing. The inhibitory and promoting effects of modifiers and dispersants are illustrated. Reduce heat treatment defects by using two diluents (HDDDA and ACMO). Zirconia parts with large overhangs can be printed without support. Parts flexural strength is 845 MPa and exhibited a high relative density (>99.2%).